Analisis Spasial Faktor-Faktor yang Mempengaruhi Kejadian Tuberkulosis di Malang Raya Tahun 2020-2021 - Olivionita, Vita; Wardani, Hartati Eko; Alma, Lucky Radita; Gayatri, Rara Warih (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Indonesia is the second country with the highest TB burden in the world. The government continues to strive for TB prevention and control to reduce TB rates. One of the efforts that can help in the TB program is by utilizing a Geographic Information System (GIS)Methods: The study is an ecological study; GIS as an approach. Data was obtained from the Health Service in Malang Raya and the Central Bureau of Statistics’ websiteResult: Study results are the pattern of distribution of TB incidence that tends to be high occurs in areas that have low coverage of healthy houses, low coverage of houses with healthy lifestyle, high population density, low air temperature, high air humidity, and high rainfall.Conclusion : The pattern of distribution of TB incidence that tends to be high occurs in areas that have low coverage of healthy houses, low coverage of houses with PHBS, high population density, high air temperature, high air humidity, and high rainfall.